2007
DOI: 10.1002/for.1001
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting inflation using economic indicators: the case of France

Abstract: In order to provide short-run forecasts of headline and core HICP inflation for France, we assess the forecasting performance of a large set of economic indicators, individually and jointly, as well as using dynamic factor models. We run out-of-sample forecasts implementing the Stock and Watson (1999) methodology. We find that, according to usual statistical criteria, the combination of several indicators-in particular those derived from surveys-provides better results than factor models, even after pre-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…4 Breitung et al (2013) analyze the predictive content of 15 daily indicators for the German inflation rate and found that predictive (MIDAS) regressions using a broad commodity price index and crude oil prices yield a regression R 2 of >0.3, whereas all other predictive regressions exhibit an R 2 of <0.10. As argued by Bruneau et al (2007), energy prices do play a dominant role in inflation forecasting, whereas exchange rates are poor predictors of inflation changes. In a similar vein, empirical results suggest that interests rates, inflation-indexed bonds, bond yields and yield spreads do not reveal any considerable predictive power.…”
Section: Daily Predictorsmentioning
confidence: 99%
“…4 Breitung et al (2013) analyze the predictive content of 15 daily indicators for the German inflation rate and found that predictive (MIDAS) regressions using a broad commodity price index and crude oil prices yield a regression R 2 of >0.3, whereas all other predictive regressions exhibit an R 2 of <0.10. As argued by Bruneau et al (2007), energy prices do play a dominant role in inflation forecasting, whereas exchange rates are poor predictors of inflation changes. In a similar vein, empirical results suggest that interests rates, inflation-indexed bonds, bond yields and yield spreads do not reveal any considerable predictive power.…”
Section: Daily Predictorsmentioning
confidence: 99%
“…Regarding the first dimension, Marcellino et al (2003) find that forecasting inflation at the country level and aggregating the forecasts increases the accuracy of euro area forecasts relative to direct forecasts at the euro area level. Regarding the second dimension, country-specific studies by Bruneau et al (2007) and Duarte and Rua (2007) and Moser et al (2007) all find that aggregating HICP component forecasts yields more accurate predictions of inflation in France, Austria and Portugal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the second dimension, country‐specific studies by Bruneau et al. () and Duarte and Rua () and Moser et al. () all find that aggregating HICP component forecasts yields more accurate predictions of inflation in France, Austria and Portugal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, factor models have been used to analyze certain marketing issues, such as human lifestyle typology (Lastovicka et al 1987), consumer behavior (Aaker 1997), and advertising (Pollay and Mittal 1993). Limited mainly by the usually short-term longitudinal data in marketing, dynamic factor models seem to be more popular in the fields of economics and finance for forecasting the co-movement of a set of gross national product data Watson 1999, 2006;García-Ferrer and Poncela 2002;Bernanke and Boivin 2003;Koop and Potter 2004;Peña and Poncela 2004;Bruneau et al 2007;Raknerud, Skjerpen, and Transportation Planning and Technology 569 Swensen 2010) and international market indices (Hu, Lin, and Kao 2008). However, the great potential of dynamic factor models in marketing research should not be overlooked when a problem with the length of data gathering does not exist.…”
Section: Introductionmentioning
confidence: 99%